IMPLEMENTASI SMART DETECTION BANJIR DI DESA BONDAR ROKAN HULU BERBASISKAN TENAGA SURYA - Samosir, Elprida; Aryza, Solly; Syahputra, M. Rizky; Anisah, Siti; Hamdani, Hamdani (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
In this study, a flood detection system that works automatically using solar power was designed by knowing the river water level. This water level monitoring system is carried out by implementing an ultrasonic sensor based on a microcontroller, which will know the level of the water level created at certain levels.